The influence of intra venous promethazine on intra venous morphine for acute pain management in the emergency department: a randomized clinical trial - Al-Hilmi, Saim (2010)
Pain is the most common presenting complaint in Emergency Department (ED). Morphine is the gold standard for treatment of pain and has unpleasant effects related to the dosage. Promethazine is among the drugs being used to treat the unpleasant effect and is believed to have analgesic component. The objective of this study is to determine the additive effect of promethazine on morphine as an analgesia in acute pain management and to investigate the adverse drug reaction of morphine in patient given promethazine. The study was conducted from August 2008 until 30 October 2009 in ED, Hospital Kuala Lumpur and Hospital Universiti Sains Malaysia (HUSM). Patients who fulfill the inclusion criteria were selected for the study. Patients were randomized into morphine with normal saline or morphine with promethazine group based on the randomization plan. Data obtained includes numerical pain score, systolic blood pressure, diastolic blood pressure, pulse rate, nausea and vomiting up to 60 minute. The researcher completed the questionnaire before patients left the ED. One hundred patients were enrolled. 28% (n=28) were female and 72% (n=72) were male. Mean age group age was 36.0 (SD 12.66) years old. 65% (n=65) of patients received morphine with normal saline and 45% (n=45) received morphine with promethazine. Mean NRS at 0 and 60 minute were 7.2 (SD 0.40) and 1.9 (SD 0.71) for morphine with normal saline and 7.2 (SD 0.40) and 1.8 (0.68) for morphine with promethazine (p=0.960). Mean systolic blood pressure at 0 and 60 minute were 139.8 (SD 7.89) and 133.4 (SD 8.20) for morphine with normal saline and 141.1 (SD 6.94) and 134.9 (SD 7.20) for morphine with promethazine (p=0.93l ). Mean diastolic blood pressure at 0 and 60 minute were 74.6 (SD 7 .97) and 71.4 (SD 6.34) for morphine with normal saline and 73.6 (SD 7.45) and 70.5 (SD 6.38) for morphine with promethazine (p=0.839). Mean pulse rate at 0 and 60 minute were 94.3 (SD 5.06) and 90.7 (SD 4.89) for morphine with normal saline and 93.8 (SD 4.75) and 90.2 (4.76) for morphine with promethazine (p=0.238). The incidence of nausea and vomiting for morphine with normal saline were 9.1% (n=5)(p=0.626) and 5.5% (n=3)(p=0.595) while morphine with promethazine were 8.9% (n=4)(p=0.626) and 4.4% (n=2)(p=0.595). All above data were no significant statistically. There is no statistically and clinically significant difference in additive effect of promethazine on morphine as analgesia in acute pain management and there was no significance of adverse drug reaction in morphine with normal saline and morphine with promethazine.